iTRAQ Proteins Analysis of Early Infected Papaya Plants with Papaya Dieback Pathogen (Asian Journal of Plant Biology, 2015)
Papaya dieback disease is characterized by the greasy water-soaked lesions and spots on leaves and crowns. Defoliation and blemished of the papaya fruits are also being observed as a result of infection by Erwinia mallotivora. In an attempt to understand the molecular mechanisms leading to the bacteria pathogenesis and the papaya plant response to infection in a compatiblereaction, protein profiling during 24 hours post infection was studied using iTRAQ mass spectrometry analysis. The bacterium was sprayed into wounded leaves of a susceptible papaya cultivar (Eksotika 1) and proteome analysis was performed. The comparison of protein patterns of the treated and the control plants were carried out by labelling the control sample with iTRAQ 8 plex reagent 113 and inoculated samples with the iTRAQ 8 plex reagent 115 whichwere then analysed by peptide mass fingerprinting and identified by searches in public databases. Biochemical changes occurring in infected tissues were observed. Among the differentially expressed proteins were enolase, maturase K, superoxide dismutase, ascorbate peroxidase, phosphoribulokinase, CT114 and a hypothetical protein with unknown function.
Keywords: Papaya, Erwinia mallotivora, protein profiling, iTRAQ mass spectrometry